Développement, lutte à la pauvreté et participation au Mexique: le cas du Yucatan rural - Labrecque, Marie France (Anthropologica, 2022)
The state of Yucatan is one of the poorest of Mexico. That is why it is a privileged setting for governmental programs designed for the eradication of poverty. The examination of these programs in a larger context shows that Mexico follows the international instructions given out by the multilateral organizations. One of these instructions concerns the participation of the populations. In this article, the author first examines the global expressions of this instruction to then turn toward some of its local interpretations in Yucatan, more especially in the henequen (sisal) region. At times when the maquiladoras (assembly factories of international capital) get settled in this region and change little by little the face of peasantry that gradually is transformed in industrial labour, it is interesting to see how an instruction such as the participation of the populations can contribute to the process of modernization and to the renewal of the "order of development."